Bad days for software. - Jones, C.
The notorious Year 2000 is not the only date dangerous to software applications. Over the next 50 years, at least 100 million applications around the world will need modification because of formatting problems with dates or date-like data. The total cost of the remedies could top US 5 trillion dollars. Those problems include: the dates at which the pricing of commodities in much of Europe switches to the Euro currency; the Global Positioning System's date rollover; the date on which Unix and C libraries roll over; and some date-like patterns used for data purposes. Early in the next century, too, the 9 digits now assigned to US social security numbers and the 10 digits allotted to telephones will no longer suffice for US citizens and required phone lines. Changes to these numbering systems will also affect software. The author details how there is a sensible way to fix such problems once and for all time, but it will take worldwide agreement. He describes how, to assess the parameters of the fix, a good starting point is to examine all known date and date-like problems, along with how computers and application software basically handle dates
Keywords: C libraries; Euro currency; Global Positioning System; Unix libraries; Application software; Computers; Date formatting problems; Date-like data; Date-like patterns; Numbering systems; Software maintenance